Research on building and developing the brand of Vietnam National Chemical Industtry Group – VINACHEM = Nghiên cứu xây dựng và phát triển thương hiệu Tập đoàn Công nghiệp Hóa chất Việt Nam – VINACHEM - Chu, Phương Linh (2020)
An overall view of VCB position in the fierce competitive market among Vietnam state-owned group brands, here in after refered to as VCB. VCB hold high position and impressive in Vietnam as discussed. However, study identified that this positon could be impacted by internal and external factors such as fierce competion in fertilizers market, raw material from other Vietnam groups and inflation owing to the global rise in oil and food prices, customer judgement in comparison with other groups, new technology in producing and tactics in advertising groups (rival among existing firms). This study revealed that ability to identify VCB is not high except some main characteristics such as chemical, fertilizers, Vietnam strong economic Group, products, Vinachem logo, Vinachem green color and friendly environment. In addition, the findings confirmed that Vinachem does not apply any tactics in advertising VCB. Therefore, it can be understood that VCB positon is essential erected from dominating in Vietnam chemical field and support of Vietnam government. In case of Vietnam Government modifies the regulation in assigning mineral resource to Vinachem, Vinachem will encounter problem in maintaining VCB position, for this reason, VCB position is not stable in Vietnam market. This study pointed out some benefits that VCB positon could support Vinachem Group such as forming strategy, reduce cost in advertising and making new products, attracting investors, creating intangible assets, protecting prestige in market, accelerating process of communication and developing human resource. Vinachem still has the gap in vision, culture, and image knowledge among Vinachem experts, leaders and partners. Vinachem should reduce the gap before they implement their advertising stratergy to publish.